Complementary or Competing Frames? The Impact of Economic and Public Health Messages on COVID-19 Attitudes. Issue 1 (19th April 2023) - Knapp, Emma R.; Smith, Brianna A.; Motta, Matthew P.
Abstract: The American reaction to the COVID-19 pandemic is polarized, with conservatives often less willing to engage in risk-mitigation strategies such as mask-wearing and vaccination. COVID-19 narratives are also polarized, as some conservative elites focus on the economy over public health. In this registered report, we test whether combining economic and public health messages can persuade individuals to increase support for COVID-19 risk mitigation. We present preliminary evidence that the combination of messages is complementary, rather than competing or polarizing. When given a message emphasizing COVID-19's negative health and economic effects in a pilot study, conservatives increased their support for a broad range of risk-mitigation strategies, while liberals maintained high levels of support. A preregistered larger- n follow-up study, however, failed to replicate this effect. While complementary frames may be a promising way to persuade voters on some issues, they may also struggle to overcome high levels of existing polarization.